Buruli ulcer community health education and medical screening in Ga South District, Ghana - Narh, Charles A.; Tetteh, Edwin; , NSPA-NMIMR; Mosi, Lydia; Yeboah-Manu, Dorothy (Frontiers in Public Health, 2025)
BackgroundBuruli ulcer (BU) is caused by Mycobacterium ulcerans (MU), but the mode of transmission is unclear. BU starts as a nodule, which can progress to ulcer if not treated. Most of the affected seek help late due to socio-cultural beliefs of the cause of the disease, leading to long treatment course and disability. Therefore, to raise awareness about the disease and detect early forms of BU cases for treatment, the National Service Personnel Association of the Noguchi Memorial Institute for Medical Research (NSPA-NMIMR) conducted BU Community Health Education and Medical Screening (BU-CHEMS) in four endemic communities in the Ga South District of Ghana.MethodBetween April–June 2010, the NSPA leadership conducted a series of seminars and media campaigns to raise public awareness about BU. Prior to the BU screening in the study communities, participants were shown BU documentaries to educate them and dispel myths about the disease. This was then followed by physical examinations for signs of BU; fine needle aspirates and/ or swabs were taken from nodules, plaques or ulcerative lesions, respectively, for laboratory confirmation of MU infection. Participants also volunteered for free medical screening - Body Mass Index (BMI, N = 58), blood pressure (N = 71) and blood group test (N = 424).ResultsThe media campaigns reached over 10 million people through national radio and TV, and the BU screening benefitted 2,500 participants. Most of the participants, 85%, were aware about the disease but not the cause. Of the 33 suspected cases identified with lesions (84.8% children), 78.8% were confirmed as positive for MU infection; representing 1,040 cases per 100,000 or 1% prevalence in the study population. All the confirmed cases commenced free BU treatment and were supported with medical supplies donated by NSPA-NMIMR to the Obom Health Centre, Ga South District. Participants with BMI ≥ 25 kg/m2 (overweight/obese, 43%) and hypertension (≥130 mmHg, 49%) received medical counselling.ConclusionThe BU-CHEMS program incentivized community participation to contribute to national BU control interventions and therefore can be further refined to complement activities of the National Buruli Ulcer Control Program (NBUCP).